2003
DOI: 10.1177/153303460300200210
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery for Brain Tumors in Pediatric Patients

Abstract: !3rain tumors represent the most common solid tumor in children. Fractionated radiation therapy has been an important treatment modality in the mUlti-disciplinary management of these tumors. Stereotactic radiosurgery is the precise delivery of a single fraction of radiation and has been an important treatment option for adult brain tumor patients. Although the use of stereotactic radiosurgery in pediatric brain tumors is much less frequent, it represents an important alternative for patients with recurrent, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
2
15
0
1
Order By: Relevance
“…Central neurocytomas usually arise from the neuronal cells of the septum pellucidum, fornix, or subependymal plate of the lateral or third ventricle, so these tumors are surrounded by cerebrospinal fluid and occur as a small tumor attached to normal structures. 7,8,10,16,26,27,31) Therefore, radiosurgery has a lower risk of radiation injury than conventional radiotherapy because of the small target volume, relatively low marginal dose for tumor growth control, and steep fall-off into the peripheral normal tissue. The present series included no complication caused by radiation-induced peripheral edema or radiation necrosis, and previous studies identified only one case of side effects (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Central neurocytomas usually arise from the neuronal cells of the septum pellucidum, fornix, or subependymal plate of the lateral or third ventricle, so these tumors are surrounded by cerebrospinal fluid and occur as a small tumor attached to normal structures. 7,8,10,16,26,27,31) Therefore, radiosurgery has a lower risk of radiation injury than conventional radiotherapy because of the small target volume, relatively low marginal dose for tumor growth control, and steep fall-off into the peripheral normal tissue. The present series included no complication caused by radiation-induced peripheral edema or radiation necrosis, and previous studies identified only one case of side effects (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…2,3,[5][6][7][8][9][10][11][12][13][14]16,19,31,32,36) They are usually located in the lateral ventricles with or without extension to the third ventricles in young adults. 2,3,8,10,19) Standard initial treatment for central neurocytomas is a total resection whenever possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of chemotherapy is not yet well defined [5,6] . In adults and children with unresectable or partially resected disease, radiotherapy can be used for treatment [6,8] . Chemotherapy is sometimes used in children in an effort to delay radiotherapy and the attendant neurocognitive side effects [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Considerable controversy exists regarding the optimal therapy of patients with LGA [5][6][7] . There have been limited publications detailing the role of stereotactic radiosurgery in the treatment of patients with LGA [8,9] . This publication presents the Indiana University experience utilizing gamma knife stereotactic radiosurgery (GKSRS) in the treatment of LGA.…”
Section: Introductionmentioning
confidence: 99%